Evaluasi Lapisan Batupasir B Formasi Bekasap Lapangan Tri Untuk Menentukan Sumur Infill - Dircia Felizarda Corbafo Siki; Irene Lisa Burara; Bambang Triwibowo (PROMINE, 2016)
B Sandstone layer of Bekasap Formation is located in Central Sumatra Basin. The well in this fieldtend to decrease of the production rate, and therefore effort should be made to raise the productionrate. One effort that can be done is to infill wells. This study aims to determine the value of propertiesof reservoir B sandstone with formation evaluation methods, so it can be a material consideration indetermining the location of infill wells. B Sandstone formation evaluation result Vsh in range of 9-29%,porosity of 22-27%, and watersaturation of 19-60%, with two infill wells proposed.